2013
DOI: 10.3389/fmicb.2013.00139
|View full text |Cite
|
Sign up to set email alerts
|

Interrelated influence of light and Ni on Trichodesmium growth

Abstract: Our previous laboratory study revealed that insufficient Ni supply can limit nitrogen fixation in Trichodesmium, a primary diazotrophic phytoplankton in the tropical and subtropical oceans. Here we show that light intensity and Ni availability interrelate to influence Trichodesmium growth. Trichodesmium growth is severely inhibited under high light (670 μE m–2 s–1) and insufficient Ni condition. On the contrary, the sufficient supply of Ni in seawater can sustain the growth of Trichodesmium under either high o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 28 publications
(46 reference statements)
3
16
1
Order By: Relevance
“…3). The results of the 24H experiment further validate the hypothesis that Ni availability and light intensity interact to influence the nitrogen fixation in Trichodesmium 10. More importantly, the 24H experiment revealed a new diel pattern of nitrogen fixation, exhibiting the maximum rate near or at the end of the light phase and with the nitrogen fixation process sustained during the dark phase for the high Ni-high light treatment (Fig.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…3). The results of the 24H experiment further validate the hypothesis that Ni availability and light intensity interact to influence the nitrogen fixation in Trichodesmium 10. More importantly, the 24H experiment revealed a new diel pattern of nitrogen fixation, exhibiting the maximum rate near or at the end of the light phase and with the nitrogen fixation process sustained during the dark phase for the high Ni-high light treatment (Fig.…”
Section: Resultssupporting
confidence: 73%
“…A previous study suggested that Trichodesmium may down regulate photosynthesis during high light at noon time to permit high nitrogenase activity15, which may allow the diazotroph to fix nitrogen under lower rates of oxygen production. However, the temporal down regulating strategy does not explain why the growth rates and nitrogen fixation rates increase with light intensity in the present and past experiments9101112. Here, we found that the nitrogen fixing process was not confined to the photoperiod when Trichodesmium was subjected to intense 12H light exposure and sufficient Ni supply.…”
Section: Discussioncontrasting
confidence: 64%
“…There was even a moderate negative relationship calculated between Trichodesmium erythraeum and light intensity (Pearson's r= -0.3, p= 0.03). Studies indicated that this diazotroph is inhibited by intense light (Ho, Chu, & Hu, 2013;Bell & Fu, 2003). This could mean that light was too strong for phytoplankton in this area during these years.…”
Section: Discussionmentioning
confidence: 97%
“…Given the elevated concentrations of Mn in the subtropical gyres (notably the NASTG) (Van Hulten et al, 2017), a Mn based SOD would be a likely candidate to replace Ni-SOD in Trichodesmium as the genome contains the gene coding for Mn-SOD as well (Dupont et al, 2008). Based on the current observations of lowest Ni concentrations in regions of known elevated nitrogen fixation, but most notably given observations elsewhere that nitrogen fixation can be stimulated by Ni additions (Ho, 2013;Ho et al, 2013;Rodriguez and Ho, 2014), it would appear Ni-SOD is the preferred SOD for nitrogen fixers in the Atlantic. However, other phototrophic organisms that are abundant in the Atlantic subtropical gyres such as the cyanobacteria Prochlorococcus and Synechococcous (Flombaum et al, 2013) also use Ni-SOD (Priya et al, 2007) and thus the role of Ni-SOD in explaining the Ni depletion pattern in the Atlantic remains speculative.…”
Section: Surface Distributionmentioning
confidence: 93%
“…It is conceivable that the lower surface concentrations of Ni in the NASTG compared to the SASTG are related to nitrogen fixation as nitrogen fixing microbes such as Trichodesmium are thought to have a relatively high Ni requirement (Nuester et al, 2012;Ho, 2013;Ho et al, 2013;Rodriguez and Ho, 2014) and estimates of nitrogen fixation are higher for the NA compared to the SA (Benavides and Voss, 2015). Our data in the West-Atlantic is consistent with this notion and the hypothesis of Schlosser et al (2014) who postulated that wet dust deposition in the Intertropical Convergence Zone (ITCZ) delivers Fe to the subtropical NA and this Fe stimulates nitrogen fixation.…”
Section: Surface Distributionmentioning
confidence: 99%